Increasing Eighth Grade Student’s Writing Skills Using Mind Mapping Technique - Putri, Chrissy Andrea (Universitas Terbuka, 2023)
Writing accelerates students' use of the target language, making it an essential part of classroom preparation. Writing skills can be improved through the use of mind mapping. The following are the research's goals: (1) to determine whether teaching writing to eighth-graders using mind mapping technique is more effective than using peer review, (2) to determine whether eighth-graders with higher levels of creativity have better writing skills than those with lower levels of creativity, and (3) to determine whether teaching methods and students' creativity interact when teaching writing to eighth-graders. This is an experimental study with a 2x2 factorial design. This study was participated by 48 students as the subject of the study. Data of this study were collected through writing and creativity tests. ANOVA and the Tukey test were used to analyze the data. The findings of the study revealed that the mind mapping technique is more effective than the peer review technique for teaching eighth-grade writing. The students with high creativity have better writing skills than students with low creativity. There is an interaction between teaching techniques and students' creativity in teaching writing in the eighth grade.